Experimental investigation of on-site degradation of crystalline silicon PV modules under Malaysian climatic condition - Islam, Mohammad Aminul; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (National Institute of Science Communication and Information Resources (NISCAIR), 2018)
Photovoltaic (PV) power plant capacity is growing very fast in Malaysia. The operating capacity of a PV plant digresses from the installed capacity after several years of operation. The degradation rate of different poly and mono crystalline silicon PV modules due to real field aging at various time spans has been detected by EL imaging, maximum power measurement and dark I-V analysis. The obtained degradation values of PV modules are 1.78, 7.06, 13.92, 17.04 and 17.42% due to ageing at a period of 8 months, 16 months, 4 years, 9 years and 11 years, respectively. The reason behind this degradation is attributed to the reduction of shunt resistance which declines gradually as result of aging. The degradation rate of a PV module has been estimated as 18.61% after 21 years of aging. Temperature coefficient of maximum power of PV module also degrades due to aging. And the rate of temperature coefficient of maximum power degradation decreases with the increase of aging period.